Efficacy Of Lyophilized Inactivated Rabies Vaccine - Omaima A. A. Alshamandy (Egyptian Society for Animal Management, 2020)
An interesting finding that emerged from the study was the difference in potency between inactivated rabies vaccines prepared in liquid and lyophilized forms. Inactivated rabies vaccine prepared from BHK21 infected cell culture in the two forms revealed that its immunogenicity was completely preserved on lyophilization. The two vaccine formulae were found to be free from foreign contaminants, safe in both inoculated mice and puppies and potent inducing high levels of specific rabies antibodies in vaccinated puppies. Such antibodies were increased gradually from the first-week post-vaccination to the same extent in the blood of immunized puppies with the lyophilized vaccine as in that of puppies immunized with liquid vaccine. These results confirmed the claim that inactivated rabies vaccines could be lyophilized with retention of potency. Considering the possible value of a stable, freeze-dried rabies vaccine that could be stored and transported with ease, it was considered desirable to confirm the above findings.